Comparison of Tidal Analysis Results at Tumumpa Coastal Fishing Port Using Least Squares Method and Admiralty Method - Lang, Abigail Emylia Febricristiani; Kalangi, Patrice N. I.; Dien, Heffry V; Masengi, K. W. A.; Pamikiran, Revols D. Ch.; Kaparang, Frangky E. (Sam Ratulangi University, 2022)
Tumumpa Coastal Fishing Port is located at 1°31'21